DOCUMENT FLOW IN ELECTRONIC MONEY TRANSACTIONS IN THE CONTEXT OF ACCOUNTING INFORMATION SUPPORT FOR FINANCIAL SECURITY (World of finance, 2023)
Introduction. The formation basis of the digital economy is the transition of business entities to electronic transactions. It is necessary to revise the order of document circulation at the enterprise, since electronic transactions involve the operation of electronic means of payment and cryptocurrencies, information about which is transferred between participants of settlement operations. First of all, the method of forming and processing primary documents in cash flow accounting will undergo changes. Accounting forms information arrays for cash management, which is an element of ensuring the financial security of enterprises.The purpose of the article is to research the transformational trends in the electronic document flow of electronic money transaction systems from the accounting point of view to ensure the financial security of enterprises.Methods. In the process of carrying out scientific research, a systematic methodical approach in combination with innovative, functional methods and methodical tools of generalization, bibliographic and comparative analysis was used to realize its aim.Results. The accounting positioning of the bank statement as a primary document improved, which replaced in the conditions of electronic communication with financial institutions by information orders on the transfer of funds to the recipient and confirmation of the receipt of a payment from the electronic transaction system. The method of generating electronic invoices for payment, receipts and other supporting documents has been optimized through the recombination of data from the electronic transaction system in traditional regulated forms for informational participation in the formation and execution of electronic contractual relations and smart contracts. It is proposed to use blockchain technology in the organization of electronic document flow in electronic money transactions to ensure the financial security of enterprises regarding: fragmentation of information with the possibility of storing each of the elements with different stakeholders; optimization of document flow management, which involves automatic identification of the type and content of documents with sending to responsible persons; elimination of information barriers (oversaturation, redundancy, insufficiency, distortion of data); storing the history of data changes, which prevents financial fraud and accidental errors. The procedure for using the electronic signature system for authenticating the official responsible for monetary transactions in the electronic transaction system and obtaining stakeholder access to confidential reporting has been clarified. An information scheme and principles of a separate software module have been developed, which is a communication platform for information synchronization between electronic money transaction services and an automated system of accounting and management of transactions, and can be implemented at various enterprises to ensure their financial security.Conclusions. The need to optimize electronic document flow in the system of electronic money transactions based on author’s proposals and developments to ensure financial security in combination with cyber protection of the enterprise. Cyber protection of electronic document management against internal and external cyber threats requires further research.